A1.05 The mer tyrosine kinase receptor plays a protective role in joint inflammation by mediating efferocytosis. (24th February 2016) - Beermann, S; Waterborg, CEJ; Bennink, MB; Lemke, G; Koenders, MI; van de Loo, FAJ
Abstract : Background and objective: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterised by a hyper-inflammatory response in synovial joints. During arthritis, increased levels of pro-inflammatory mediators are present in the joint cavity attracting leukocytes of which many undergo apoptosis. One receptor involved in uptake of apoptotic cells is the Mer receptor tyrosine kinase. In addition, the Mer receptor is involved in an anti-inflammatory natural feedback mechanism of Toll-like receptor signalling. The main ligand for Mer is Protein S ( Pros1 ), acting as a bridge between apoptotic cells and the Merreceptor on phagocytic cells. Our objective was to elucidate the role of Mer in experimental arthritis. Materials and methods: KRN serum transfer arthritis was induced in either Mer-deficient mice or in wild type mice that overexpress Pros1 in their knee joints. Mice were macroscopically scored and at day 7 or 14, respectively, knee joints were taken for histology. In collagen-induced arthritis (CIA), mice were intravenously injected with a commercially available Mer-specific antibodies or an adenovirus overexpressing Pros1 . At day 30 or 31, respectively, knee joints were taken for histology and immunohistochemical staining of active Caspase-3. Results: In Mer-deficient mice, induction of passive KRN arthritis enhanced the macroscopic score in both knee and ankle joints compared to wild type. In addition, increased cartilage and bone erosion was found in knee joints of Mer -/- mice. Intra-articular overexpression of Pros1 before KRN serum injections markedly reduced arthritis severity in wild type mice. CIA mice treated with Mer-specific antibodies showed increased incidence and higher macroscopic knee score compared to those receiving an isotype control (IgG). Histological analysis showed significantly enhanced synovial inflammation and bone erosion. In addition, significantly more active Caspase-3 positive cells were present, a marker for apoptotic cells. This indicates reduced efferocytosis in the anti-Mer treated animals. In concordance with these data, CIA mice which systemically overexpressed Pros1 showed a significant reduction in knee inflammation. Conclusion: These data indicate the importance of Mer in controlling the severity and resolution of inflammation in experimental arthritis. Our data suggest that promoting Mer-mediated uptake of apoptotic cells in the arthritic joint might be therapeutically beneficial.